The Role of Physical Activity in Managing Urological Health - Hubert Bigajski; Aleksandra Banaś; Maciej Michalik; Piotr Widera; Marta Handschuh; Olga Bilczewska; Justyna Helis; Wiktoria Janik; Paulina Jakubczyk; Aleksandra Buczek (Quality in Sport, 2025)
Introduction and Purpose